Pembinaan Masyarakat Awam dalam Penggunaan Alat Kontrasepsi di Desa Samiran - Yulia Paramita Rusady; Rohilah Rohilah (Pusat Riset dan Inovasi Nasional, 2024)
The use of a computerized system to determine the number of children and the severity of their illness is called a family plan. Allowed family planning is an effort to regulate or thin out births or an effort to prevent pregnancy temporarily with the agreement of husband and wife due to certain situations and conditions for the benefit of the family, society, and the state, thus family planning here has the same meaning as regulation of offspring. The goal after a brief coaching is expected to increase knowledge and understanding in choosing contraceptives according to needs and as an effort to make the government's program to have 2 children better. The activities carried out in the form of coaching and brief socialization using Manikin and leaflets. The results of fostering family planning acceptors are able to increase mother's knowledge in choosing types of contraception and understand the advantages and disadvantages of each contraceptive. The conclusion in this community service is that the mother's knowledge of contraceptives increases so that she can choose the right contraceptive.